Effect of Empathic Tones on Spelling Ability among Native Arab Children - Ibrahim, Raphiq; Badarny, Samih (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Little research has been conducted on the development of spelling in general and in the Arabic language in particular. In this research, we intend to examine the effect of empathic tones in words on the accuracy of spelling. The study included 162 elementary school children. They were asked to spell concrete nouns, including frequently and less frequently used words, from literary and spoken Arabic containing both empathic and non-empathic tones. Significant effect of empathic tones on spelling accuracy was found. This manifested itself in a better spelling performance of words without empathic tones than in words with empathic tones. The research results reinforce a specific characteristic of Arabic orthography and emphasize the need for appropriate intervention to improve the spelling abilities of children.